Expressions figées dans une perspective multilingue : problèmes d’équivalence et de traduction - Sułkowska, Monika (Neophilologica, 2008)
The aim of the article is to present the issue of an interlinguistic equivalence of phraseological units and the problem of their translation. In the first part of the text, the author of the article attempts to define and characterise the notion of phraseologism on the basis of the current research in this field. What follows is the notion of equivalence and its short historical description. In the main, third part of the text, the author of the work in question describes the results of her study conducted on the basis of the corpus of phraseological units in French, Italian and Polish. In final, the text is devoted to practical methods a translator may use when transla ting phraseological units.